Keterjaminan Perkembangan Psikis Anak Usia Dini Korban Perceraian Ditinjau Dari Aturan Hukum Positif - Laras Shesa (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2021)
The purpose of the study is to find out whether in positive legal rules such as child protection laws and child welfare discuss about psychic developments that are part of the child's spiritual survival guarantee. If there is any whether it has become a guarantee for the smooth development of early childhood psychically is not just in material fulfillment. This study is a study that uses qualitative methods that refer to earlier sources of libraries and researches that support library data. With the normative description approach of positf hocumes relating to child rights and obligations. The results of the study showed that in the rule of the positive Law in Indonesia still only generally redaction of the guaranteed needs of child psychic development. What’s more, regarding the child who was a victim of divorce, but at least in article 156 The Islamic Law Compilation of point C could already be a solution in the event of a problem. So that the guarantee of child psychic survival cannot yet be normatively measured even more so in its application. So far what is seen in the positive hokum rules is simply a guarantee for the fulfillment of the living of material for the child.